Organophosphate Toxicity Presenting with Cholinergic Crisis, Intermediate Syndrome and Delayed Polyneuropathy in Succession: a Rare Presentation - Malkarnekar, S; L, Naveen; Adam, S Reddy (International Journal of Medical Toxicology and Forensic Medicine, 2014)
Background: Organophosphate (OP) self poisoning is a major health hazard in a predominantly agrarian country like India. Acute cholinergic crisis and intermediate syndrome are well recognized manifestations of OP toxicity, delayed polyneuropathy being an unusual clinical event. Case Report: We describe a 30-year-old male with suicidal chlorpyrifos poisoning who presented with cholinergic crisis; developed intermediate syndrome subsequently and ultimately three weeks later landed up with OP induced delayed polyneuropathy (OPIDPN). Conclusion: This reported case emphasizes on the importance of strict vigilance and follow up in patients with OP toxicity in order to recognise and appropriately treat chronic toxicities like OPIDPN.